Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Pengelola Usaha Mikro Kecil dan Menengah (UMKM) dalam Membayar Pajak - Ramadhan, Ahmad Fikri; Umaimah, Umaimah (Universitas Muhammadiyah Gresik, 2025)
The growth of micro, small and medium enterprises in Gresik Regency should have an impact on increasing regional income, but it has not contributed much to regional tax revenue. Therefore, this study aims to test the effect of self-assessment implementation on tax compliance of MSME managers in Gresik Regency. This study uses a descriptive quantitative method that takes 84 respondents through the Slovin formula on MSME managers in Gresik Regency. Data were collected using a Likert model questionnaire. The results of the multiple linear regression analysis obtained a value of t = 4.159 and p = 0.000 (p <0.05) which means that self-assessment has a positive and significant effect on taxpayer compliance; and a value of t = 4.707 with p = 0.000 (p <0.05) indicates that tax planning has a positive and significant effect on taxpayer compliance.